EXPERIMENTAL AND NUMERICAL ANALYSIS OF FRETTING FATIGUE CRACK INITIATION IN DOVETAIL JOINT FOR AERO ENGINE COMPRESSOR - Hassan, Z. U.; I. Hammouda, M. M.; Khushnood, S.; Jahanzeb, M.; Malik, A.; Akhtar, K. (The Nucleus, 2012)
This paper presents the development of a unique, safe and flexible fretting fatigue experimental test rig for analysis of fretting fatigue crack initiation in dovetail joint of aero-engine compressor. The testing rig is capable for revolving the specimen disc and blades in the range of 0 ~ 20,000 rpm and reverse back to zero rpm in small increments. Different experimental test rigs already designed by various researchers were evaluated on the basis of their capability. This conceptual design test rig is unique addition in the fretting fatigue testing field and is helpful for testing of different type of joints and materials. The experiments for bakelite and structural steel have been performed and conclude that the edge of common surface near the dovetail notch base is the fretting fatigue failure of the disc. The modeling and simulation has been carried out using commercially available software. It is found in each iteration analysis irrespective of thickness and material of the disc, fillet is the weakest portion in the model.